2009
DOI: 10.1016/j.csr.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms controlling the air–sea flux in the North Sea

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 38 publications
6
45
2
Order By: Relevance
“…Thus understanding the interactions between our actions (and their subsequent effects) and the efficiency of the BP and MCP are of particular importance, both for understanding the likely response to future global change and in informing whether or how marine management options might be employed to enhance (or reduce degradation of) pump efficiency. Many of the interactions over which we may be able to exercise management options take place in shelf seas, which are active areas for DOM cycling (Prowe et al, 2009;Johnson et al, 2013) and carbon export (Tsunogai and Noriki, 1991;Thomas et al, 2004). Although covering only 8 % of the ocean's surface area, they account for 20 % of the ocean's capacity to absorb CO 2 (Thomas et al, 2004).…”
Section: Relevance To Societymentioning
confidence: 99%
“…Thus understanding the interactions between our actions (and their subsequent effects) and the efficiency of the BP and MCP are of particular importance, both for understanding the likely response to future global change and in informing whether or how marine management options might be employed to enhance (or reduce degradation of) pump efficiency. Many of the interactions over which we may be able to exercise management options take place in shelf seas, which are active areas for DOM cycling (Prowe et al, 2009;Johnson et al, 2013) and carbon export (Tsunogai and Noriki, 1991;Thomas et al, 2004). Although covering only 8 % of the ocean's surface area, they account for 20 % of the ocean's capacity to absorb CO 2 (Thomas et al, 2004).…”
Section: Relevance To Societymentioning
confidence: 99%
“…1 and 2). Using the results of experimental work performed at the Institute of Oceanology PAS and literature data (Thomas and Schneider, 1999;Omstedt et al, 2004;Lass and Matthäus, 2008;Prowe et al, 2009), it was found that temporal resolutions of the variables should be finer than one week for concentrations of carbon species, and one day for water volumes and directions. Hence, three latitudinal transects in the Danish Straits were selected, for which hydrological data were supplied from the DMI-BSHcmod three-dimensional (3-D) ocean circulation model, which is the Danish Meteorological Institute (DMI) operational model.…”
Section: Carbon Exchange Between the Baltic Sea And The North Seamentioning
confidence: 99%
“…In process-based numerical models, alkalinity and dissolved inorganic carbon (DIC) are considered explicit state variables (master variables used to solve the carbonate system) that are transported by physical processes and modified by chemical and biological processes Prowe et al, 2009;Artioli et al, 2012;Turi et al, 2014;Fiechter et al, 2014). Also, this approach is not free from deficiencies, as it implies the need to explicitly parameterize the major known relationships among DIC, alkalinity and the biogeochemical processes, and to define exactly which chemical compounds are considered in the definition of the alkalinity.…”
Section: Introductionmentioning
confidence: 99%